Genistein inhibition of OGD-induced brain neuron death correlates with its modulation of apoptosis, voltage-gated potassium and sodium currents and glutamate signal pathway. (25th July 2016) - Ma, Xue-ling; Zhang, Feng; Wang, Yu-xiang; He, Cong-cong; Tian, Kun; Wang, Hong-gang; An, Di; Heng, Bin; Liu, Yan-qiang
Abstract: In the present study, we established an in vitro model of hypoxic-ischemia via exposing primary neurons of newborn rats to oxygen–glucose deprivation (OGD) and observing the effects of genistein, a soybean isoflavone, on hypoxic-ischemic neuron viability, apoptosis, voltage-activated potassium (Kv ) and sodium (Nav ) currents, and glutamate receptor subunits. The results indicated that OGD exposure reduced the viability and increased the apoptosis of brain neurons. Meanwhile, OGD exposure caused changes in the current-voltage curves and current amplitude values of voltage-activated potassium and sodium currents; OGD exposure also decreased GluR2 expression and increased NR2 expression. However, genistein at least partially reversed the effects caused by OGD. The results suggest that hypoxic-ischemia-caused neuronal apoptosis/death is related to an increase in K + efflux, a decrease in Na + influx, a down-regulation of GluR2, and an up-regulation of NR2. Genistein may exert some neuroprotective effects via the modulation of Kv and Nav currents and the glutamate signal pathway, mediated by GluR2 and NR2. Highlights: Genistein inhibits hypoxic-ischemia-caused neuronal apoptosis/death. Genistein reverses increase in K + efflux in hypoxic-ischemic neuron. Genistein reverses decrease in Na + influx in hypoxic-ischemic neuron. Genistein reverses down-regulation of GluR2 in hypoxic-ischemic neuron. Genistein reverses up-regulation of NR2 in hypoxic-ischemic neuron.